Aberrant crypt foci and microadenoma as markers for colon cancer. - Archer, M C (1992)
Foci of aberrant crypts similar to those seen in experimental animals exposed to colon carcinogens have been identified and quantified on the mucosal surface of fixed resections of human colon after methylene blue staining. Many of the foci in humans showed dysplasia on histologic examination and were considered to be microadenoma (MA). These lesions may be precursors for adenomatous polyps and colorectal cancer. Rats and mice initiated with azoxymethane, then fed diets containing sucrose or casein heated at 180 degrees C to stimulate normal cooking conditions, had three to five times more large MA after 100 days than controls. Thus, cooked sugar and protein contain promoters of the growth of colonic MA. 5-Hydroxymethylfuraldehyde was identified as a promoter in cooked sugar.